Association between leptin, adiponectin and resistin and long-term progression of hand osteoarthritis. Issue 7 (6th April 2011) - Yusuf, Erlangga; Ioan-Facsinay, Andreea; Bijsterbosch, Jessica; Klein-Wieringa, Inge; Kwekkeboom, Joanneke; Slagboom, P Eline; Huizinga, Tom WJ; Kloppenburg, Margreet
Abstract : Objective: To investigate the association between baseline serum adipokines levels—leptin, adiponectin and resistin—and long-term progression of hand osteoarthritis (HOA). Methods: Baseline and 6-year radiographs of 164 patients (mean age 60 years, 81% women) with HOA (defined as a Kellgren and Lawrence score ≥2 in at least two hand joints) were assessed for joint space narrowing (JSN) in 32 hand joints using the Osteoarthritis Research Society International atlas. Progression was defined as a change in the sum of the JSN score above the smallest detectable change of 2, reflecting change above measurement error. Serum adipokines were measured at baseline and patients were categorised by adipokine tertiles. RRs (and 95% CI) of HOA progression for patients in the second and third tertiles were calculated relative to the first tertile, using generalised estimating equations. Adjustments were made for age, sex and body mass index. Results: Patients in the two highest tertiles of adiponectin had a decreased risk of 70% (RR=0.3 (0.2 to 0.7)) for HOA progression in comparison with patients in the lowest tertile. Leptin and resistin levels were not associated with progression. Conclusion: Adiponectin levels are associated with progression of HOA, suggesting that adiponectin may be involved in the pathophysiology of OA.